Case report: Targeting the PD-1 receptor and genetic mutations validated in primary histiocytic sarcoma with hemophagocytic lymphohistiocytosis - Zhao, Yan; Deng, Yating; Jiang, Yi; Zheng, Wenli; Tan, Yanlin; Yang, Zhiwu; Wang, Zhihua; Xu, Feng; Cheng, Zhao; Yuan, Lingli; Peng, Hongling (Frontiers in Immunology, 2023)
Histiocytic sarcoma (HS) is a rare hematological malignancy with limited treatment options, and it is also prone to complications such as hemophagocytic lymphohistiocytosis (HLH) in the later stages of the disease, leading to difficulties in treatment and poor prognosis. It highlights the importance of developing novel therapeutic agents. Herein, we present a case of a 45-year-old male patient who was diagnosed with PD-L1-positive HS with HLH. The patient was admitted to our hospital with recurrent high fever, multiple skin rashes with pruritus throughout the body and enlarged lymph nodes. Subsequently, pathological biopsy of the lymph nodes revealed high expression of CD163, CD68, S100, Lys and CD34 in the tumor cells and no expression of CD1a and CD207, confirming this rare clinical diagnosis. Concerning the low remission rate by conventional treatment in this disease, the patient was administered with sintilimab (an anti-programmed cell death 1 [anti-PD-1] monoclonal antibody) at 200 mg/d combined with a first-line chemotherapy regimen for one cycle. Further exploration of pathological biopsy by using next-generation gene sequencing led to the use of targeted therapy of chidamide. After one cycle of combination therapy (chidamide+sintilimab, abbreviated as CS), the patient achieved a favorable response. The patient showed remarkable improvement in the general symptoms and laboratory examination results (e.g., elevated indicators of inflammation); even the clinical benefits was not persistent, he survived one more month after his cessation of treatment by himself due to economic difficulty. Our case suggests that PD-1 inhibitor coupled with targeted therapy might constitute a potential therapeutic option for primary HS with HLH.